2012
DOI: 10.1074/jbc.m111.332676
|View full text |Cite
|
Sign up to set email alerts
|

Transient P2X7 Receptor Activation Triggers Macrophage Death Independent of Toll-like Receptors 2 and 4, Caspase-1, and Pannexin-1 Proteins

Abstract: Background: P2X 7 receptors are thought to be primarily involved in inflammatory signaling. Results: Transient (1-4 min) high ATP induced delayed (hours) cell death in macrophages from WT and TLR2/4, Casp1, or Panx1 knock-out mice. Conclusion: Transient P2X 7 receptor activation triggers macrophage-selective apoptotic cell death independent of TLR signaling, Casp1, and Panx1. Significance: P2X 7 receptors function foremost as death triggers in macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 41 publications
(79 reference statements)
2
63
1
1
Order By: Relevance
“…It is well known that P2X7 activation by ATP participates in the regulation of the innate response in macrophages, including the killing of intracellular pathogens, the release and maturation of proinflammatory cytokines (i.e., IL-1b and IL-18) (51-55), and the increase in PGE 2 levels (19). The mechanisms involved in these actions implicate a rise in Ca 2+ influx and in the activation of the MAPK signaling pathways (56)(57)(58). However, less is known regarding the role of P2Y receptors in macrophage function.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that P2X7 activation by ATP participates in the regulation of the innate response in macrophages, including the killing of intracellular pathogens, the release and maturation of proinflammatory cytokines (i.e., IL-1b and IL-18) (51-55), and the increase in PGE 2 levels (19). The mechanisms involved in these actions implicate a rise in Ca 2+ influx and in the activation of the MAPK signaling pathways (56)(57)(58). However, less is known regarding the role of P2Y receptors in macrophage function.…”
Section: Discussionmentioning
confidence: 99%
“…One difficulty in the effort to better understand this question is the fact that often researchers use the ATP-dependent cationic dye uptake as a measure of pannexin-1 involvement in a particular phenomenon [9,67,71]. However, we [10] and others [11] showed that the P2X7-dependent dye uptake has at least two associated pathways, with differences between cations and anions.…”
Section: Discussionmentioning
confidence: 89%
“…Hanley and collaborators showed that activation of P2X7R induces blebbing, uptake of cationic dyes, caspase-3/7 activation, and cell death independent of caspase-1 and pannexin-1 [67]. P2X7R-dependent blebbing involves both Ca 2+ -dependent and Ca 2+ -independent mechanisms [52,[68][69][70] and is dissociated from IL-1β secretion or capase-1 activation [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the early events may be transient, as part of the yet undefined ''find me'' signals, or alternatively they may take different pathways resulting in cell death. In conjunction with activation of the P2X7 receptors, as it has been already shown in melanoma cells (Hanley et al 2012), for example, one could postulate that by mediating apoptotic actions of extracellular nucleotides this may have a potential role in clinical practice as a novel therapeutic target. It also appears that the hepatocytes are more sensitive and susceptible to these early intracellular events leading to apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Recent publications indicated that P2X7 receptor activation and Ca 2? overload may act as a death trigger for native mouse macrophages independent of Pannexin 1 and proinflammatory caspase-1 and TLR signaling (Hanley et al 2012;Jalilian et al 2012;Nishida et al 2012). YP1 positivity may be an early indicator of P2X7 receptor activation.…”
Section: Introductionmentioning
confidence: 99%